Potential of Hermetia illucens Larvae as an Alternative Prey in Enhancing Predatory Efficiency and Reproductive Success of Sycanus annulicornis - Wildan Muhlison; Irwanto Sucipto; Zulfa Maulida; Muhammad Usman; Budianto (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Predatory insects are essential in controlling pest populations; however, their ability to work depends on prey availability and quality. This study investigates the potential of alternative prey to enhance the predatory efficiency and reproductive success of Sycanus annulicornis, a generalist predator used in pest management. The research assessed predation behavior, longevity, and reproductive capacity of S. annulicornis when fed with Hermetia illucens, Tenebrio molitor, and Alphitobius diaperinus. Choice and no-choice tests revealed a significantly higher predation rate for H. illucens (98.0 ± 50.25 for females and 89.0 ±14.0 for males; P < 0.05) compared to T. molitor (67.0 ± 15.4 for females, 54.2 ± 11.2 for males) and A. diaperinus (67.0 ± 12.1 for females, 65.5 ± 17.0 for males). Longevity analysis showed that females fed H. illucens lived significantly longer (49.7 ± 1.00 days, P < 0.05) than those consuming T. molitor (41.2 ±6.46 days) or A. diaperinus (41.3 ± 8.45 days). Reproductive performance was highest for H. illucens, with fecundity (33.1 ± 22.0 eggs) and fertility (27.5 ± 18.7%) exceeding that of T. molitor (24.5 ± 13.1 eggs, 10.0 ± 4.4%) and A. diaperinus (30.3 ± 22.3 eggs, 19.0 ± 12.7%). This study supports using H. illucens as a nutritionally adequate prey for mass rearing S. annulicornis, improving its application in biological pest control.